BOLESŁAW PRUS READS BOURGET. EMANCIPATION, SPIRITISM AND NOVEL THEORY - Jauksz, Marcin (Porównania, 2013)
Published in “Kurier Codzienny” in 1889 Bolesław Prus’s review of Paul Bourget’s novel The Disciple is a starting point for this reflection on Polish writer’s literary theory, who in the late 80s starts to collect his “reflections on composition”. In the context of the famous polemic with Aleksander Świętochowski, Emancypantki – Prus’s novel published in the early 90s and the press discussion in Warsaw of the winter of 1893, the author of the article attempts to highlight those of the reflections which show how deep was Prus’s belief in a possibility to shape the reader’s moral conduct through literature, literature which would promote truths different from the ones that make Bourget’s characters’ lives so miserable.